2009
DOI: 10.1159/000255461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Symptomatic Charcot-Marie-Tooth Disease in Iceland: A Study of a Well-Defined Population

Abstract: Background/Aim: To determine the prevalence and clinical spectrum of Charcot-Marie-Tooth disease (CMT) in Iceland. Methods: We identified all individuals with symptomatic CMT, based on information from all practicing neurologists, both neurophysiology laboratories and the only neurology department in the country. The diagnosis was based on clinical features and neurophysiological testing. DNA testing was regarded as confirmatory. Results: We identified 37 individuals in 18 families, which were not linked by id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
1
19
0
2
Order By: Relevance
“…This presents a problem in identifying cases of CMT, and most prevalence studies have included a number of individuals with few or no symptoms that were only discovered when seemingly unaffected family members were studied. This may explain the somewhat higher prevalence found in some studies [21]. …”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This presents a problem in identifying cases of CMT, and most prevalence studies have included a number of individuals with few or no symptoms that were only discovered when seemingly unaffected family members were studied. This may explain the somewhat higher prevalence found in some studies [21]. …”
Section: Discussionmentioning
confidence: 84%
“…However, in relation to diagnostic methods used in studies, neurophysiological findings and family history with multiple affected individuals can further support the diagnosis of CMT, which is the most common inherited neuropathy [20]. The systematic screening of multiple close relatives is important [21,22]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review on the epidemiology of CMT identified 103 potentially relevant studies, but only 12 studies met the inclusion criteria and 10 studies reported on CMT prevalence [20]. Indeed, population-based studies on the epidemiology of inherited polyneuropathies are quite few [14,21,22,23] and many of them preceded the era of modern molecular diagnostics [24,25]. Instead, there are more studies describing the frequency of CMT and its subtypes in clinical series [6,26,27,28,29] including one figure that is based on unpublished data from Finland [30,31].…”
Section: Discussionmentioning
confidence: 99%